2022
DOI: 10.1080/20016689.2022.2154418
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of infant hypoallergenic formulas to manage cow’s milk protein allergy in France

Abstract: Background Clinician’s choice of hypoallergenic formulas in the first-line management of cow’s milk protein allergy (CMPA) should be informed by evidence on clinical efficacy and cost-effectiveness. Objective We compare the cost-effectiveness of amino acid-based formula (AAF), extensively hydrolyzed casein formula with Lactobacillus rhamnosus Gorbach Goldin (EHCF+LGG), extensively hydrolyzed whey formula (EHWF), and rice hydrolyzed formula (RHF) in non-breastfed childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…29 Another important point is the cost-effectiveness of HRPF; in fact, in a recent study, hypoallergenic formulas accounted for the largest proportion of the total cost of managing CMPA, averaging 69% across all comparators, with a minimum of 58% for HRPF and a maximum of 87% for amino acid-based formulas. 30 However, according to the ESPGHAN position paper, 31 it is important to consider the arsenic content of HRPFs, as this is not stated for all commercial HRPFs. 32 Therefore, only HRPFs whose the arsenic content is known and within the recommended limits should be used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Another important point is the cost-effectiveness of HRPF; in fact, in a recent study, hypoallergenic formulas accounted for the largest proportion of the total cost of managing CMPA, averaging 69% across all comparators, with a minimum of 58% for HRPF and a maximum of 87% for amino acid-based formulas. 30 However, according to the ESPGHAN position paper, 31 it is important to consider the arsenic content of HRPFs, as this is not stated for all commercial HRPFs. 32 Therefore, only HRPFs whose the arsenic content is known and within the recommended limits should be used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent survey of Spanish paediatricians on this topic showed that HRPF was indicated as the second preferred alternative formula after EHF, and that more than 80% of paediatricians believed that HRPF was better accepted by infants in terms of organoleptic qualities compared to EHF, as far as taste preferences are concerned 29 . Another important point is the cost‐effectiveness of HRPF; in fact, in a recent study, hypoallergenic formulas accounted for the largest proportion of the total cost of managing CMPA, averaging 69% across all comparators, with a minimum of 58% for HRPF and a maximum of 87% for amino acid‐based formulas 30 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Martin et al indicates that eHCF combined with LGG is the most costeffective strategy for treating CMA in the United Kingdom ( 39 ). According to a French study conducted by Paquete et al, the combination of eHCF and LGG was associated with longer symptom-free periods, greater immune tolerance, and reduced costs ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Martin et al indicates that eHCF combined with LGG is the most cost-effective strategy for treating CMA in the United Kingdom [39]. According to a French study by Paquete et al, the combination of eHCF and LGG was associated with longer symptom-free periods, greater immune tolerance, and reduced costs [40].…”
Section: Discussionmentioning
confidence: 99%